Investigating mobile home parks as affordable housing in Riley County, Kansas - Jennings, Kylee Rose (Kansas State University, 2024)
The United States is in an affordable housing crisis, where in no state can a minimum wage employee, working 40-hour weeks afford a market rate apartment. Manufactured housing has been and continues to be a significant source of unsubsidized affordable housing for the American public. Manufactured, or mobile homes, are most often found in mobile home parks (MHPs) or manufactured housing communities (MHCs). A large majority of these communities are owned by wealthy landlords who may never see, improve, or care about the community but benefit from the profit MHCs generate. Mobile or manufactured homeowners on the site do not see significant wealth gain through this particular type of homeownership. This vulnerable group is subject to prejorative stereotypes or stigmas, predatory lending, exclusionary zoning, ownership problems, and a lack of place-making. The urban design of MHPs is rarely considered outside of economics, leaving residents subject to a lack of privacy. Existing literature on MHCs is focused on the Southern US, emphasizing disaster mitigation and recovery. Further MHCs in the Great Plains and Kansas have been rarely studied. To understand the conditions of MHPs in this area and the lives of the people who live in them, in this thesis, I ask how are mobile homes acting as affordable housing in Riley County, Kansas, and how does the urban design of MHPs affect residents’ lives? Using data collected through a survey and semi-structured interviews with residents, park officials, and public officials, I find that MHPs in Riley County, while being more affordable than the market rate option, suffer from exclusionary zoning, deceptive affordability, and quasi-homeownership, which denies the benefits of wealth gain and urban design. My recommendations based on this work are grouped into two categories- ways to find alternative affordable housing, so mobile home park residents have greater choices when searching for housing, and ways to eliminate precarity that currently exists in MHPs, which will better protect the residents who live there.
Keywords: Mobile home parks; Affordable housing; City planning; Riley County; Home-ownership; Urban design